Morphometric response of solanum lycopersicum with disconnected soil in urban terraces - Coro Mendoza, Mercy Jovanna (2025)
Soil contamination by heavy metals is a growing problem due to human activity, especially in horticultural crops such as tomatoes, which are widely demanded by industry and fresh consumption. Disconnected soil, which has lost the natural cohesion between its components, can cause infertility, desertification and loss of biodiversity. In this context, the research aimed to evaluate the morphometric response of Solanum lycopersicum in disconnected soil. The study was carried out at the Experimental Center “La Playita” in La Maná, Ecuador, using an experimental design with four treatments and five replications. Variables such as plant height, stem diameter, leaf length, number of flowers and cluster height were evaluated. The results showed that the treatment with the highest proportion of organic substrates (T4) favored plant growth and development, especially in height, stem diameter and number of flowers. These findings are relevant for the optimization of agronomic strategies and yield improvement of horticultural crops in urban agroecological systems.